2003
DOI: 10.1590/s0102-35862003000600009
|View full text |Cite
|
Sign up to set email alerts
|

Achados histológicos e sobrevida na fibrose pulmonar idiopática

Abstract: Background: Idiopathic pulmonary fibrosis was recently redefined as usual interstitial pneumonia of unknown etiology. Consequently, the prognostic value of histological findings needs to be reassessed. Objective: To correlate clinical, functional and histological findings with survival in patients with idiopathic pulmonary fibrosis. Method: Patients (n = 51; mean age: 66 ± 8 years; gender: 21 females/30 males) were evaluated. Of the 51, 26 were smokers or ex-smokers. Duration of symptoms, forced vital capacity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
7

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 24 publications
1
4
0
7
Order By: Relevance
“…(2,27,28) In this study, this finding was significantly more common in the left lower lobes. However, one group of authors, having found no such association, questioned the prognostic value of fibroblastic foci in isolation.…”
Section: Resultssupporting
confidence: 49%
“…(2,27,28) In this study, this finding was significantly more common in the left lower lobes. However, one group of authors, having found no such association, questioned the prognostic value of fibroblastic foci in isolation.…”
Section: Resultssupporting
confidence: 49%
“…Os achados característicos são áreas microscópicas de pulmão normal alternadas com lesões em graus variáveis (GROSS et al, 2001;COLETTA et al, 2003;COTTIN et al, 2004).…”
Section: Objetivounclassified
“…O infiltrado celular consiste de macrófagos, linfócitos e células plasmáticas, com o agravamento da doença, são maiores a proliferação fibroblástica e o envolvimento pulmonar por cicatrização colagênica (GROSS et al, 2001;KING et al, 2001;COLETTA et al, 2003;SCOTT et al, 2004).…”
Section: Objetivounclassified
See 2 more Smart Citations